2014
DOI: 10.1016/s1474-4422(14)70094-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms, diagnosis, and treatment of neurocysticercosis

Abstract: The infection of the nervous system by the cystic larvae of Taenia solium (neurocysticercosis) is a frequent cause of seizure disorders. Neurocysticercosis is endemic or presumed to be endemic in many low-income countries. The lifecycle of the worm and the clinical manifestations of neurocysticercosis are well established, and CT and MRI have substantially improved knowledge of the disease course. Improvements in immunodiagnosis have further advanced comprehension of the pathophysiology of this disease. This k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
543
1
58

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(617 citation statements)
references
References 133 publications
(153 reference statements)
15
543
1
58
Order By: Relevance
“…In the infected animals, the majority of the cysticerci were located inside the lateral ventricles accompanied by a discrete-to-moderate intensity of inflammatory response. This fact was previously reported in studies that showed that the mere presence of the parasite's antigens are responsible for the development of inflammatory alterations and ventriculomegaly, which may lead to cerebrospinal fluid obstruction 22,23 . Zepeda et al 21 showed that T. crassiceps antigens are able to induce inflammation in the brain tissue and apoptosis of hippocampal cells.…”
Section: Discussionsupporting
confidence: 53%
“…In the infected animals, the majority of the cysticerci were located inside the lateral ventricles accompanied by a discrete-to-moderate intensity of inflammatory response. This fact was previously reported in studies that showed that the mere presence of the parasite's antigens are responsible for the development of inflammatory alterations and ventriculomegaly, which may lead to cerebrospinal fluid obstruction 22,23 . Zepeda et al 21 showed that T. crassiceps antigens are able to induce inflammation in the brain tissue and apoptosis of hippocampal cells.…”
Section: Discussionsupporting
confidence: 53%
“…Para establecer el diagnóstico definitivo y el tipo de enfermedad se requiere la tomografía computarizada (TC) y/o la imagen por resonancia magnética (RM); sin embargo, son procedimientos muy costosos, poco disponibles en zonas endémicas y en muchos pacientes no se obtienen resultados claros debido a la ubicación cerebral o al estado de desarrollo del cisticerco. Por esta razón, se utilizan pruebas serológicas como ayudas diagnósticas; no obstante, en muchos ensayos se han reportado datos de sensibilidad y especificidad muy bajas, por lo que actualmente sólo se utiliza de rutina el ensayo inmunoenzimático de electrotransferencia (EITB) para la detección de anticuerpos y el inmunoensayo ligado a enzimas (ELISA) para la detección de antígenos o anticuerpos, que además de presentar alta sensibilidad y especificidad, son menos costosos, más asequibles en zonas endémicas, lo que deriva en un menor tiempo de diagnóstico, tratamiento oportuno y disminución de las secuelas de la enfermedad [15][16][17] .…”
Section: Artículo Originalunclassified
“…A recent review on NCC showed that MRI findings are better predictive for the stage of the cysts and diffusion-weighted images and apparent diffusion coefficient maps allowing better demonstration of the cysticerci in their colloidal phase. Calcified cysts were described as not well depicted and there was a suggestion that more sophisticated sequences, as susceptibility-weighted protocols, would be necessary 9 . Cavernous malformations, on the other hand, are not well seen on CT images, where the lesions will range from non-visualization to the mildly enhancing ones, variable format and, very often, with calcification.…”
Section: The Quest For the Neuroimagingmentioning
confidence: 99%
“…Carpio detected that the proportion of the seropositivity in epileptic NCC patients was the same reported in the general population in the same geographic areas 3 . On the other hand there is a chance of dual disease, like temporal lobe epilepsy with hippocampal sclerosis and NCC, in endemic regions, being involved in the pathogenesis of epilepsy in patients diagnosed with NC and the differential diagnosis will only be reached by means of special neurophysiological testing 9 . Evidence-based data from well designed prospective studies to establish the surrogates for epilepsy due to NCC is scarce 3,10,11,12 , showing the importance of differential diagnosis with other diseases on the determination of NCC as seizures etiology and the risk of overestimation of neurocysticercosis as a prime cause of seizures.…”
mentioning
confidence: 99%